Analisis Financial Distress Dengan Metode Altman Z-Score Untuk Memprediksi Kebangkrutan - Puspitasari, Ajeng; Pratiwi, Ni Made Ida; Nasution, Ute Chairuz (Jurnal Dinamika Administrasi Bisnis, 2017)
This study aims to determine the financial condition of plastic and packaging industry companies using the ratio analysis of finance method Altman (1968), so as to predict the potential occurrence of financial distress conditions in the company period 2013-2015. The sample consisted of 10 plastic and packaging industry companies listed in Indonesia Stock Exchange (BEI), and selected by purposive sampling. Research data in the form of annual financial statements that have been audited in plastic and packaging industry companies listed on the Indonesia Stock Exchange (BEI). The data analysis technique used is the financial ratio analysis of Altman method (1968). The final results of this study indicate that the financial ratios of Altman method (1968) can predict the condition of financial distress in plastic and packaging industry companies listed on the Indonesia Stock Exchange.Â Kata Kunci: Financial Distress, Altman Finance Ratio (1968)